Answer

Step by step solution by experts to help you in doubt clearance & scoring excellent marks in exams.

Updated On: 26-7-2021

Apne doubts clear karein ab Whatsapp par bhi. Try it now.

CLICK HERE

Loading DoubtNut Solution for you

Watch 1000+ concepts & tricky questions explained!

2.0 K+

99

Text Solution

-1013

Answer :

BSolution :

`because " Adj"U = ((-1,-2,0),(-7,-5,-3),(9,-6,3))` <br> `therefore U^(-1) =("Adj"U)/abs(U) = ("Adj"U)/3` <br> `rArr` sum of the elements of <br> `U^(1) = 1/3(-1-2+0-7-5-3+9+6+3)=0`